Non-invasive assessment of the presence and severity of cardiac amyloidosis. A study in familial amyloidosis with polyneuropathy by cross sectional echocardiography and technetium-99m pyrophosphate scintigraphy. Issue 3 (September 1984) - Eriksson, P; Backman, C; Bjerle, P; Eriksson, A; Holm, S; Olofsson, B O
Abstract : Twelve patients with familial amyloidosis with polyneuropathy were examined both by cross sectional echocardiography and by technetium-99m pyrophosphate scintigraphy to assess involvement of the heart non-invasively. All 12 patients had echocardiographic abnormalities. The most prominent findings were highly refractile myocardial echoes, thickened heart valves, and increased thickness of the heart walls. Four patients had abnormal myocardial uptake of technetium-99m pyrophosphate. The remaining eight had equivocal or no myocardial uptake and were considered to have normal scintigrams. A certain amount of amyloid is probably required to produce an abnormal scintigram, although lesions with less amyloid can evidently be identified by echocardiography. Neither the duration of polyneuropathy nor its severity showed any relation to the echocardiographic or scintigraphic findings. It is concluded that cross sectional echocardiography is superior to technetium-99m pyrophosphate scintigraphy in detecting cardiac involvement in familial amyloidosis with polyneuropathy and that these results may also be applicable to other forms of amyloidosis.